MicroRNA-30a Modulates Type I Interferon Responses to Facilitate Coxsackievirus B3 Replication Via Targeting Tripartite Motif Protein 25 - Li, Jia; Xie, Yewei; Li, Liwei; Li, Xiaobing; Shen, Li; Gong, Jin; Zhang, Rufang (Frontiers in Immunology, 2021)
Viral myocarditis is caused by a viral infection and characterized by the inflammation of the myocardium. Coxsackievirus B3 (CVB3) infection is one of the most common among the infections caused by this virus. The host’s early innate immune response to CVB3 infection particularly depends on the functions of type I interferons (IFNs). In this study, we report that a host microRNA, miR-30a, was upregulated by CVB3 to facilitate its replication. We demonstrated that miR-30a was a potent negative regulator of IFN-I signaling by targeting tripartite motif protein 25 (TRIM25). In addition, we found that TRIM25 overexpression significantly suppressed CVB3 replication, whereas TRIM25 knockdown increased viral titer and VP1 protein expression. MiR-30a inhibits the expression of TRIM25 and TRIM25-mediated retinoic acid-inducible gene (RIG)-I ubiquitination to suppress IFN-β activation and production, thereby resulting in the enhancement of CVB3 replication. These results indicate the proviral role of miR-30a in modulating CVB3 infection for the first time. This not only provides a new strategy followed by CVB3 in order to modulate IFN-I–mediated antiviral immune responses by engaging host miR-30a but also improves our understanding of its pathogenesis.